Robotic theatre: comparative analysis of human and mechanized activities in the creative process - Sovhyra, Tetiana (Creativity Studies, 2021)
The article systematizes and analyzes the existing experience of organizing the creative process in a robotic theater. The author explores the robotic theater phenomenon, the artificial intelligence technology possibilities to function in the stage space. The article provides a comparative analysis of human and mechanized interaction in the stage space. The methodological basis of the research is a combination of several methods: analytical – for accounting for historical and fictional literature; theoretical and conceptual method – for analyzing the conceptual and terminological system of research and identifying the specifics of introducing the artificial intelligence technology in creative process; comparative-typological – to compare the peculiarities of the functioning of mechanized “actors” with the acting skills of human performers. The article explores the threat perception and uncanny valley concepts to study the perception of a robot–actor by an audience. The author examines the process of human interaction with a robotic body: from the moment of interest, interaction to the moment of rejection of the robot by a person (audience).